Florida's Introduced Birds: European House Sparrow (Passer domesticus) - Steve A. Johnson; Heather Violett (EDIS, 2009)
WEC-260, a 7-page illustrated fact sheet by Steve A. Johnson and Heather Violett, describes this small, seed-eating bird which nests on buildings in urban areas — similar species, native range and habitats, mode of introduction, introduced range and habitats, ecology, ecological impacts, impacts on people and pets, solutions, and how you can help. Includes additional resources. Published by the UF Department of Wildlife Ecology and Conservation, June 2009.